DOI: 10.18130/v3cq2q
|View full text |Cite
|
Sign up to set email alerts
|

The Pneumatology of Brevard S. Childs

Abstract: Baker Academic, 2011) 29. For more on the topic of the change in Childs' thought, see the introduction in: Daniel R. Driver, Brevard Childs: Biblical Theologian (Grand Rapids: Baker Academic, 2010) 2-3. Driver eventually concludes, "That Childs' thought develops over time does not make it a moving target." I would agree. 12 Brevard Childs, Biblical Theology in Crisis (Philadelphia: Westminster, 1970) 92. 13 Ibid., 99. 14 Ibid., 105.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Since the gaugino phases are identically zero and the range of ϕ Ae is severely restricted by correlations between A and M at the string scale, the cancellations are insufficient in this particular scenario. Therefore, only a very small fraction of the ϕ µ − ϕ Ae parameter space leads to models allowed by the electron EDM, in direct analogy with the dilaton-dominated scenario in the perturbative heterotic models discussed in [18].…”
Section: B Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the gaugino phases are identically zero and the range of ϕ Ae is severely restricted by correlations between A and M at the string scale, the cancellations are insufficient in this particular scenario. Therefore, only a very small fraction of the ϕ µ − ϕ Ae parameter space leads to models allowed by the electron EDM, in direct analogy with the dilaton-dominated scenario in the perturbative heterotic models discussed in [18].…”
Section: B Resultsmentioning
confidence: 99%
“…For the sake of simplicity, we assume the string scale and the GUT scale coincide, and that the gauge couplings unify at this scale. Thus, in the first model we consider with SU(3) and U(1) Y arising from the same brane sector, the boundary conditions (17) and (18) are implemented at the GUT scale, and the parameters are subsequently evolved down to the electroweak scale. The sparticle masses and the CPviolating phases depend on the free parameters m 3/2 , θ, Θ i , i = 1, 2, 3, which are related by Θ 2 1 +Θ 2 2 +Θ 2 3 = 1, as well as the two phases α 1 and α 2 .…”
Section: B Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that in the universal case, as in the minimal supergravity models, the prediction of the asymmetry is less than 2%, since in this case the electric dipole moments (EDM) of the electron and neutron constrain the SUSY CP-violating phases to be very small [2,3]. Furthermore, it is also known that in this case, one can not get any sizeable SUSY contribution to the CP-violating observables, ε and ε ′ /ε [4][5][6][7]. The impact of flavour structure in the non-degenerate A-terms, which is expected in string inspired models, has been studied [6][7][8].…”
mentioning
confidence: 99%